Prevalence of Hepatitis B Virus in Hemodialysis Patients Infected with Hepatitis C Virus in Mosul District / Iraq - Al-Taan, Ghusoon Saadoon Hasan; Khalid, Mohammed Dawag (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Most problematic infection haemodialysis (HD) are at higher risk for acquiring Hepatitis B virus (HBV) and Hepatitis C virus (HCV) infections than the general population. Patients and Methods This study was carried out between January 2018 until July 2018, a total of (60) blood samples were collected from hemodialysis patients. The samples tested against anti-HCV, HBsAg anti-HBS and anti-HBC IgM, using ELISA technique and determination HBV-DNA, HCV-RNA viral load by Real time polymerase chain reaction. Results Prevalence HCV RNA was 12(20%) out of 60 patients were RT-PCR positive for HCV RNA with viral load, up to 100.000, Copy/ml and 10(16.69%) out of 60 patients were RT-PCR positive for HBV DNA in both positive and negative HCV RNA patients group with average viral load more than 100.000 copy/ml., 3 Patients out of 12 (25%) HCV RNA, positive patients were also positive for HBV DNA, while 40 (66%) out of 60 patients were anti-HBSAg positive, while the positivity of anti-HBCoIgM was 5 (50%). Conclusion The prevalence of co-infection hepatitis B and C was high in hemodialysis patients in Mosul district/Iraq